Permeability of the implanted central catheter - A literature review - Ramada, Diana (2018)
Totally implantable catheter (CVCTI) is a type of central venous catheter that becomes an essential resource because it increases the options available for intravenous therapy. Its handling is not free of complications. There are many controversies about the most appropriate solution to maintain its permeability. In this context, it was intended to determine the effectiveness of a heparin solution compared to sodium chloride 0.9% in the permeability of implanted ports in adults with oncology disease. A literature review was carried out using the online databases Tripdatabase, EbscoHost (CINAHL Complete and MEDLINE), PubMed, Nursing Reference Center and Scientific Research, between September 26 and October 20, 2016. Four articles were selected. Studies suggest that there is no evidence of a different effectiveness between heparin and sodium chloride 0.9%, for the maintenance of the permeability of CVCTI. Due to the lack of evidence in this field, we believe that further studies and randomized trials are necessary.